2019
DOI: 10.1002/wrna.1563
|View full text |Cite
|
Sign up to set email alerts
|

Cluster miRNAs and cancer: Diagnostic, prognostic and therapeutic opportunities

Abstract: MiRNAs are class of noncoding RNA important for gene expression regulation in many plants, animals and viruses. MiRNA clusters contain a set of two or more miRNA encoding genes, transcribed together as polycistronic miRNAs. Currently, there are approximately 159 miRNA clusters reported in the human genome consisting of miRNAs ranging from two or more miRNA genes. A large proportion of clustered miRNAs resides in and around the fragile sites or cancer associated genomic hotspots and plays an important role in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 283 publications
(333 reference statements)
0
31
0
Order By: Relevance
“…These cancers are usually difficult to treat and this study showed the potential of RNAi-based therapies. These strategies are very versatile, as they can be used to target multiple genes or miRNAs together, which otherwise is very difficult to accomplish [238].…”
Section: Protein-based Effectorsmentioning
confidence: 99%
“…These cancers are usually difficult to treat and this study showed the potential of RNAi-based therapies. These strategies are very versatile, as they can be used to target multiple genes or miRNAs together, which otherwise is very difficult to accomplish [238].…”
Section: Protein-based Effectorsmentioning
confidence: 99%
“…Another characteristic of these miRNAs is the formation of clusters in various cancers and their acting as modulators for important cell functions. It has been noted that these clusters usually reside very near to the known cancerous sites or genomics hotspots and play a very important role in carcinogenesis [59,60]. We identified two members of the miRNA let family hsa-let-7c/b targeting KRT5 and GABBR2, involved in molecular functions such as G-protein-coupled signaling, protein binding and structural activity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miRNAs as a tumor suppressors or oncogenes has been ascertained in tumor initiation and progression. 23 Despite their short length (up to 24 nucleotides), they are involved in the regulation of many genes expression. 24 In this study, through analyzing two microarray data show the most interactions with DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the importance of noncoding RNAs in various malignancies is becoming more and more defined. The role of miRNAs as a tumor suppressors or oncogenes has been ascertained in tumor initiation and progression 23 . Despite their short length (up to 24 nucleotides), they are involved in the regulation of many genes expression 24 .…”
Section: Discussionmentioning
confidence: 99%